EXPERIENCE OF FOREIGN COUNTRIES IN PUBLIC DEBT MANAGEMENT - G. A. Mataibaeva; M.M. Valiyeva (Academic Journal of Physical and Chemical Sciences, 2019)
In recent decades, the problem of public debt is an urgent problem in most countries of the world. Despite the implementation of a number of measures and initiatives aimed at curbing the growth of global debt, its size continues to grow. At the same time, the increase in debt volumes is observed not only in developing countries experiencing a lack of their own resources, but also in a number of developed countries that have significant domestic savings, such as the United States, Japan, and the United Kingdom. Therefore, the effective management of public debt and its direct reduction are among the main priorities of the public policy of any country. Government debt does not always symbolize problems in the economy, but it can be judged on its vulnerability to external influence. What is described in detail by the authors of the article as a result of this research, in particular, effective management of public debt in foreign countries